The Silly Season - Shrimsley, Bernard (London Robson Books, 2003)
Jack Stack, a no-nonsense cockney, takes over as editor of the beleaguered "Mercury" and transforms the formerly respectable newspaper into the most tabloid of all tabloids. But has he met his match in Marina Marshall, - the chairman's mistress and the most canny columnist in Fleet Street?
English Fiction.
Keywords: Newspaper editors -- Great Britain -- Tabloid newspapers